The Asymmetric Alternate Arm Converter: A Compact Voltage Source Converter Design for HVDC - Soto Sanchez, Diego Enrique; Hernandez, M.; Andrade Aguero, Ivan Eric; Pena, R. (My University, 2018)
The Modular Multilevel Converter (MMC) has become one of the most practical topologies for integration of renewable energy power plants into the grid, through submarine HVDC cables and HVDC lines. Nonetheless, the MMC requires significant large DC storage capacitors to mitigate for large power, low frequency pulsations due to the single-phase like AC to DC conversion process in their arms. This work addresses the recently introduced Asymmetric Alternate Arm Converter, a hybride MMC topology which uses modular converter arms only on the lower side of the main converter whereas the upper side uses only standard ON-OFF valves topology. This converter is similar to the Alternate Arm Converter (AAC) but dispenses of the modules on the upper side and of the director switch on the lower side. Like the AAC, the Asymmetric AAC offers a significant reduction in DC energy storage requirements and in the number of modules. In addition, the Asymmetric AAC offers a less restricted operation than the AAC, in terms of operating over a wide range of AC to DC voltage ratio, and the possibility of achieving both distortion-free AC current and ripple-free DC current. The principle of operation of the Asymmetric AAC is revisited here and a suitable control strategy to demonstrate its operation is developed. In addition, requirements for energy storage, voltage and current rating of converter modules and converter losses are examined by means of simplified analyses. Proposals are verified through simulation studies and experiments conducted on a low power prototype having three H-bridge modules per arm. Results confirm good operation of the proposed converter and control scheme.
Keywords: alternate arm converter; hybrid multilevel converter; modular multilevel converter; hvdc